THE CONCEPT OF CRIMINAL JUSTICE SYSTEM AND CORPORATE CRIMINAL LIABILITY IN INDONESIA - Suriadiata, Irpan (Jurnal Meta-Yuridis, 2025)
The Criminal Justice System and Corporate Criminal Liability in Indonesia focuses on the imposition of legal sanctions on corporations involved in criminal acts. Under Indonesian law, corporations are recognized as legal subjects that can be held criminally liable. This study aims to: (1) examine the regulation of corporate criminal sanctions in Indonesian legislation, and (2) analyze the forms of criminal punishment and sanctions imposed on corporations in Indonesia. The research adopts a normative legal approach, utilizing statutory and conceptual analyses. The findings indicate that: (1) corporate criminal sanctions are regulated in various laws, including Law No. 7 of 1955 on Economic Crimes, Law No. 6 of 1984 on Post, Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, Law No. 8 of 1999 on Consumer Protection, Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption, and Law No. 15 of 2002 in conjunction with Law No. 25 of 2003 on Money Laundering. (2) Criminal sanctions for corporations in Indonesia are stipulated in Article 10 of the Criminal Code (KUHP). The imposition of fines on corporations aims to reduce their economic rights. The types of sanctions that may be imposed on corporations include principal sanctions and additional sanctions